Analysis of the Legal Position of Public Officials in the Indonesian Legal System (International Forum of Researchers and Lecturers, 2025)
This article discusses the legal position of public officials in the Indonesian legal system. Public officials play a crucial role in carrying out government functions and community services. This article analyzes the legal basis governing the duties and powers of public officials, as well as the responsibilities and legal protections they have. Through a review of relevant laws and regulations, this article identifies the legal challenges faced by public officials in carrying out their duties, including issues related to corruption, abuse of authority, and accountability. Using a normative juridical approach, this article offers recommendations for strengthening the legal position of public officials in order to increase efficiency and integrity in public services in Indonesia.